A Pilot Study of Bone Marrow Transplantation in a GALT‐Null Rat Model of Classic Galactosemia - Shauna A. Rasmussen; Madelyn M. Seemiller; Ingrid Smith; Madeleine Wilson; Jennifer M. I. Daenzer; Keenan Wiggins; Judith L. Fridovich‐Keil (JIMD Reports)
ABSTRACT Classic galactosemia (CG) is a rare inborn error of metabolism with substantial unmet medical need. Early detection, often by population newborn screening, enables immediate and life‐long dietary restriction of galactose, which is the current standard of care. This treatment minimizes or prevents the potentially lethal acute symptoms of disease in infants but fails to prevent the long‐term developmental complications experienced by most patients later in childhood. Many possible approaches to improved intervention have been proposed, ranging from small molecule inhibitors or effectors to chaperones to DNA or RNA‐based gene therapy, among others. Here, we describe the results of a pilot study testing the potential efficacy of GALT+ bone marrow transplantation (BMT) as a candidate intervention in a GALT‐null rat model of CG. Specifically, we pre‐treated adolescent GALT‐null rats with busulfan for myeloablation and then administered major histocompatibility complex (MHC)‐matched GFP+ bone marrow cells harvested from either GALT+ or GALT‐null donors. Successful engraftment of GALT+ but not GALT‐null cells resulted in > 50% wild‐type levels of GALT activity in red blood cells (RBC) and normalized RBC galactose‐1‐phosphate, a biomarker commonly followed in CG patients. However, GALT activity and galactose metabolites in both liver and brain samples remained essentially unchanged, demonstrating that successful GALT+ BMT in adolescent GALT‐null rats was not protective of other tissues.